Let's talk 2 : - Jones, Leo (Cambridge Univ. Press, 2002)
A teacher's manual is availble for each of the three levels of let's Talk. For each unit of the Teacher's Manual contains: vocabulary glossaries, procedures suggesting how to use the material, answers or possible answers to many of the activities...